PENGGUNAAN MEDIA BERBASIS VIRTUAL LABORATORY PADA MATERI MOMENTUM TERHADAP HASIL BELAJAR KELAS X SMAN 2 PARIAMAN - era agustriani (Universitas Negeri Padang, 2018)
In developing countries, a teacher must be active and creative role in improving the quality of education, one of them by increasing the motivation of students to learn. This study discusses the use of virtual media in learning physics laboratory on the momentum of the material and simple harmonic motion to the results of class X student of SMAN 2 Pariaman. The purpose of this study is to describe the process improvement and learning skills of students using tracker software on momentum materials and simple harmonic motion class X SMAN2 Pariaman. This type of research is (pre-experimental desing) which in this study there are external variables that influence the formation of the dependent variable. The subjects were students of class X SMAN2 Pariaman, totaling 30 people. The research was conducted in three cycles comprising the steps of (1) planning, (2) implementation, (3) completion. Data collected there are 2, namely the non-test and test data. Non-test Data obtained from the observation and assessment rubrics, while the test data in the form of post-test given to students. Based on the results of research carried out can be concluded the following points. First, using media tracker software in the process of learning can increase student motivation in learning physics. It can be seen from the improvement of student learning outcomes while studying physics using tracker software. The second study using this software can be used by students in learning physics student records must try to try to use the software independently. This can be evidenced by the influence gained by 25.7% in the same direction, and significant for knowledge and competence 11.5% in the same direction for competency skills.